Effects of yeast, culture selco and Isochrysis galbana on the nutritional value of rotifers (Brachionus plicatilis) as food for turbot larvae - Fernández-Reiriz, María José; Labarta, Uxío; Planas, Miguel; Rodríguez, José Luis (1993)
14 pages, 2 figures, 6 tables.-- ICES Symposium on Mass Rearing of Juvenile Fish, Bergen, 21-23 June 1993 Turbot larvae were reared on two types of enriched rotifers (B.plicatilis). Enrichment of rotifers was made on I. galbana (24 h). Previous to enrichment, the rotifers were cultured on baker's yeast and then on Culture Selco (from Artemia Systems S.A.) (R2) or only on baker's yeast (Rl). One group of larvae (L1) fed on R1-enriched rotifers and another group (L2) fed on R2-enriched rotifers. The biochemical composition (protein, total lipids, lipid classes and fatty acids) of the rotifers, prior to and during enrichment, and larvae is studied. The effect of the use of Culture Selco prior to the enrichment of the rot if ers was a significative increase in the relative content of total protein, total lipids and neutral lipids in the rotifers. The effect was found even after enrichment. However, non significant differences were found between the two groups of laivae, except for protein which was higher in the group L1. Growth of L2 was better but not statistically significant from that of L1. The consequence of the use of Culture Selco prior to the rotifer enrichment was a significative increase in some fatty acids essential for turbot larvae (20:4n-6, 20:5n-3 and 22:6n-3). The fatty acid composition of L1 and L2-larvae showed a marked drop in the content of the main fatty acids during the culture. However, a slight recuperation in the content was found on day 8. At this time the absolute content of 20:4n-6; 20:5n-3 and 22:6n-3 was higher in L2 , although not statistically different from that of L1. The content of n-3 HUFA in R2-enriched rotifers (0.72% dry weight) is significantly higher than in R1-enriched rotifers (0.23% dry weight). However, non significant differences were found between the two groups of larvae Peer reviewed